Adverse Donor Reaction During and Immediately After Venesection - Mahbub-ul-Alam, M; Hyder, M Shamim; Khan, MB Karim; Islam, M Answarul (TAJ: Journal of Teachers Association, 2009)
There are no reports in the transfusion medicine literature that describe adverse donor reactions after whole-blood donation based on solicited information. A descriptive study was done in the Transfusion Medicine Department, Dhaka Medical College Hospital during the period of July 2000 to December 2001. The present study solicited adverse donor reaction and donor reaction information from 14,413 randomly selected whole-blood donors approximately immediately or within 30 minutes after the whole-blood donation. From this study, percentage of adverse donor reaction was 4.98%. The number of prior donations was inversely proportional to the risk of reaction; It was found that, first-time donors have a higher frequency of reactions (5.04%) than do repeat donors (4.96%).The value for first-time or repeated donor were significant (p<0.0001).Female donors are more vulnerable to adverse donor reaction than male donors (5.97%) (4.94%) (p<0.001). In this study it was also found that, fainting or vasovagal attack was more common in female donors (0.77 %) than male donors (0.35 %). It was also found incidence were more in first time donor (1.08%) than repeated donor (0.0%) in case of female donor. Adverse donor reaction after donation and complaints may be more common than previously thought. The post donation follow-up and interview is a good tool for defining the blood donor's experience. It can also be used to evaluate and potentially improve blood donor safety and comfort. doi: 10.3329/taj.v20i1.3088 TAJ 2007; 20(1): 39-47